Parkin mitochondria in the autophagosome - McBride, Heidi M. (The Rockefeller University Press, 2008)
Narendra et al. (see p. 795 of this issue) have made an exciting new discovery that links the fields of mitochondrial quality control and the genetics of Parkinson's disease (PD). Through an elegant series of high-resolution imaging experiments, they are the first to provide evidence that the PARK2 gene product Parkin is selectively recruited to damaged or uncoupled mitochondria. This recruitment leads to the clearance of the organelles through the autophagosome, demonstrating a primary function for Parkin in the regulation of mitochondrial turnover. This work significantly increases our understanding of PD and provides a new framework for the development of therapeutic interventions.